The Pristine Inner Galaxy Survey (PIGS): IX. the largest detailed chemical analysis of very metal-poor stars in the Sagittarius dwarf galaxy - Sestito, Federico; Vitali, Sara; Jofre, Paula; Venn, Kim A.; Aguado, David S.; Aguilera-Gómez, Claudia; Ardern-Arentsen, Anke; Silva, Danielle de Brito; Carlberg, Raymond; Eldridge, Camilla J. L.; Gran, Felipe; Hill, Vanessa; et al. (Astronomy and astrophysics, 2024)
The most metal-poor stars provide valuable insights into the early chemical enrichment history of a system, carrying the chemical imprints of the first generations of supernovae. The most metal-poor region of the Sagittarius dwarf galaxy remains inadequately observed and characterised. To date, only ∼4 stars with [Fe/H] < −2.0 have been chemically analysed with high-resolution spectroscopy. In this study, we present the most extensive chemical abundance analysis of 12 low-metallicity stars with metallicities down to [Fe/H] = −3.26 and located in the main body of Sagittarius. These targets, selected from the Pristine Inner Galaxy Survey, were observed using the MIKE high-resolution spectrograph at the Magellan-Clay telescope, which allowed us to measure up to 17 chemical species. The chemical composition of these stars reflects the imprint of a variety of type II supernovae (SNe II). A combination of low- to intermediate-mass high-energy SNe and hypernovae (∼10 − 70 M⊙) is required to account for the abundance patterns of the lighter elements up to the Fe-peak. The trend of the heavy elements suggests the involvement of compact binary merger events and fast-rotating (up to ∼300 km s−1) intermediate-mass to massive metal-poor stars (∼25 − 120 M⊙) that are the sources of rapid and slow processes, respectively. Additionally, asymptotic giant branch stars contribute to a wide dispersion of [Ba/Mg] and [Ba/Eu]. The absence of an α−knee in our data indicates that type Ia supernovae did not contribute in the very metal-poor region ([Fe/H] ≤ −2.0). However, they might have started to pollute the interstellar medium at [Fe/H] > −2.0, given the relatively low [Co/Fe] in this metallicity region.